Determinants of youth unemployment in Bhutan - YANGCHEN, Tashi (KDI School, 2017)
Youth unemployment is a global issue and Bhutan is no exception. The youth unemployment rate of 9.4% for 2014 in Bhutan is not so high compared to other countries but it is a concern given its size of population. (MoLHR, Labour Market Information and Bulletin,2013-2014).This study examines, how the determinants such as age, qualification, place, gender and types of training contribute to youth unemployment and to what extent does it affect in Bhutan. My result shows that youth unemployment is high in urban area and also among youth who has higher qualification and training level.
Thesis(Master) --KDI School:Master of Public Policy,2017